Morphologically Controlled Thermal Rate of Ultra High Performance Concrete. Issue 1800 (8th June 2015) - Cupkova, Dana; Yao, Shi-Chune; Azel, Nicolas
ABSTRACT: This research focuses on defining the design principles that integrate passive-system thinking into the built environment with the goal of mitigating building energy usage by self-regulating the heat gain/loss at level of building envelopes. In collaboration with TAKTL, a company that developed and uses advanced Ultra High Performance Concrete (UHPC) integrated with mold design and manufacturing of architectural elements, our research targets how specific manipulation of UHPC surface area in combination with self-regulating thermochromic response can improve building's energy performance. By coupling the adaptive color response with surface geometry we can suggest new passive sustainable solutions that would mitigate the energy usage with no additional energy input; purely through designing the form and color adaptation for UHPC concrete Trombe wall components integrated within building façade systems. This paper outlines the first part - the thermal behavior in response to surface geometry. Such comprehensive knowledge not only enhances the possibilities within architectural design, but becomes an effective strategy in self-regulating the heat gain/loss at the building surface level, while reducing the need for mechanical building systems.